스피루리나 첨가 쌀엿강정의 품질 특성 - 심은경(Eun Kyoung Shim); 김효진(Hyo Jin Kim); 김혜란(Hye Ran Kim); 김미리(Mee Ree Kim) (東아시아食生活學會誌, 2010)
Riceyeotgangjung (RYG) with added spirulina was prepared with citron juice for masking of odor. Oil temperature for puffing was found to be $220^{°}C$ for frying dry rice based upon the results of expansion rate and color. RYGs with added spirulina (1, 2, and 3%) were prepared under the above conditions, and their physicochemical and sensory properties were examined under storage at $60^{°}C$ for 15 days. Moisture content of RYG decreased proportionally with the spirulina content and storage time. The hardness levels of the freshly made RYGs with spirulina were higher than that of control. During storage, the hardness of the control gradually increased, but those of the RYGs with spirulina gradually decreased, although no significant differences existed between the spirulina containing RYGs. Lightness and redness values in the Hunter color system decreased according to the spirulina content and storage time. Yellowness value also increased with the spirulina content and storage time. Phycocyanin and total phenolic content increased with spirulina content, but decreased with the storage period. Sensory evaluation results showed that RYG with 2% added spirulina received the highest scores for color, taste, overall acceptability, and intention of purchase. As a result, the optimal addition amount of spirulina to RYG is recommended to be 2%.